2016
DOI: 10.4103/1119-3077.179287
|View full text |Cite
|
Sign up to set email alerts
|

Rhinoscintigraphic analysis of nasal mucociliary function in patients with Bell's palsy

Abstract: This study showed a faster MCT rate on the nonparalyzed side in Bell's palsy patients when compared to the paralyzed side and the control subjects. A compensatory mechanism could be the underlying reason for faster MCT on the nonparalyzed side. Further studies on larger patient groups are needed to investigate the effect of facial paralysis on the MCT and changes of facial nerve function on the opposite, nonparalyzed side of the face.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…32 In another study, it was found using the rhinocintigraphic method that the NMTR of patients with Bell's palsy on the non-paralyzed side was statistically significantly faster compared to healthy persons and the paralyzed side of patients with Bell's palsy whose parasympathetic functions were affected. 27 In our study, rhinoscintigraphy showed that NMCR values decreased and t½ values enhanced as ELF-MFs intensity increased. Based on these results, exposure to ELF MFs may cause dose-dependent changes in parasympathetic function.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…32 In another study, it was found using the rhinocintigraphic method that the NMTR of patients with Bell's palsy on the non-paralyzed side was statistically significantly faster compared to healthy persons and the paralyzed side of patients with Bell's palsy whose parasympathetic functions were affected. 27 In our study, rhinoscintigraphy showed that NMCR values decreased and t½ values enhanced as ELF-MFs intensity increased. Based on these results, exposure to ELF MFs may cause dose-dependent changes in parasympathetic function.…”
Section: Discussionsupporting
confidence: 57%
“…Binboga et al concluded that short‐term exposure of the chest area to ELF‐EMF could change parasympathetic innervation 32 . In another study, it was found using the rhinocintigraphic method that the NMTR of patients with Bell's palsy on the non‐paralyzed side was statistically significantly faster compared to healthy persons and the paralyzed side of patients with Bell's palsy whose parasympathetic functions were affected 27 . In our study, rhinoscintigraphy showed that NMCR values decreased and t½ values enhanced as ELF‐MFs intensity increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations